2006
DOI: 10.1111/j.1472-765x.2006.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of agar plate and real-time PCR on enumeration of Lactobacillus, Clostridium perfringens and total anaerobic bacteria in dog faeces

Abstract: Aims:  To compare agar plate and real‐time PCR methods on enumeration of total anaerobic bacteria, Lactobacillus and Clostridium perfringens in dog faeces. Methods and Results:  Thirty‐two faecal specimens from Labrador retriever dogs were used to compare agar plate and real‐time PCR enumeration methods for Lactobacillus, C. perfringens and total anaerobic bacteria. Total anaerobic bacteria, C. perfringens and Lactobacillus of faeces were counted (as CFU g−1 faeces) for 48‐h incubation at 37°C in an anaerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 21 publications
(39 reference statements)
0
26
0
1
Order By: Relevance
“…Faecal total bifidobacteria counts at M0, M2 and M3 were measured using quantitative Real-Time Polymerase Chain Reaction (RT PCR) (18)(19)(20)(21). Briefly, we used 1 mL aliquots of faecal samples to extract total DNA of bacterial populations by means of a commercial kit (QIAmp DNA Stool Mini Kit; Qiagene, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Faecal total bifidobacteria counts at M0, M2 and M3 were measured using quantitative Real-Time Polymerase Chain Reaction (RT PCR) (18)(19)(20)(21). Briefly, we used 1 mL aliquots of faecal samples to extract total DNA of bacterial populations by means of a commercial kit (QIAmp DNA Stool Mini Kit; Qiagene, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Due to sampling difficulty, the canine intestinal LAB microbiota has been studied mainly from feces (9,11). However, it is argued that fecal samples cannot represent the microbiota present in the upper gut since they are different niches and provide specific habitats for different microbiota (17).…”
mentioning
confidence: 99%
“…The significant correlation between the cfu of the OZF cells obtained by two methods indicated that it is possible to use DNA copy to estimate the number of bacteria. The plate counts and the results of qPCR assays were also found in good agreement for different target LAB species by Furet et al [12], Neeley et al [36], and Fu et al [11]. Additionally, Matsuda et al [32] determined the viable cell counts with a LIVE/DEAD BacLight bacterial viability kit, RT-qPCR, and conventional culture methods.…”
Section: Discussionmentioning
confidence: 71%